2021
DOI: 10.3390/vaccines9111321
|View full text |Cite
|
Sign up to set email alerts
|

Association between COVID-19 Vaccine Side Effects and Body Mass Index in Spain

Abstract: COVID-19 vaccines have shown high efficacy, with most side effects being mild–moderate and more frequently reported by females and people at younger ages. Since no studies have assessed the impact that weight status could have on the reported adverse reactions, we aim to study the association between weight status and reported side effects. We included data on 2136 adults from an online survey conducted from 6 May to 9 June 2021. The questionnaire was filled in by participants over Google forms. Generalized Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 29 publications
9
42
5
2
Order By: Relevance
“…Specifically, we found that females had a statistically significant probability of risk for injection site pain and swelling, fatigue, chills, dizziness, nausea, and feeling unwell after Vaxzevria vaccine. These findings are in agreement with previous works reporting lower adverse effects in males [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, we found that females had a statistically significant probability of risk for injection site pain and swelling, fatigue, chills, dizziness, nausea, and feeling unwell after Vaxzevria vaccine. These findings are in agreement with previous works reporting lower adverse effects in males [ 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the comparison of age groups showed that participants aged 20 to 39 years were more likely to experience almost the majority of post-vaccination side effects, and they constituted the largest proportion of participants who suffered from severe side effects. Studies on different populations also showed that the side effects of different COVID-19 vaccines were significantly more frequent in younger individuals compared to in the elderly [ 11 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of solicited AEs in the mRNA-1273 group were grade 1–2 in severity and generally resolved within a few days in both studies. The difference in incidence rate of solicited AEs might be due to the same vaccine dose being administered to participants in Japan and US irrespective of mean body mass, which was higher among the US participants [15] . In the present study, mean body mass index was 22.39 (±2.65) kg/m 2 in the mRNA-1273 arm whereas in the US study participants had a mean body mass index of 29.3 (±6.9) kg/m 2 [5] .…”
Section: Discussionmentioning
confidence: 97%